The Impact of Robotic Technology on Nursing Care: A Systematic Review - Sylvia Rosa Enjelina Bastian; Muflih Muflih; Deden Iwan Setiawan (Peneliti Teknologi Teknik Indonesia, 2024)
The rapid development of technology has given birth to various sophisticated innovations, one of which is robot technology. In the context of today's evolving nursing world, attention to nurses' ability to deal with technological developments, including the use of robots, is becoming increasingly important to consider the steps that need to be taken in order to achieve and maintain patient health with the help of robots as intelligent tools. The aim of this study was to thoroughly assess the impact of the use of robotic technology in nursing care through a systematic review of relevant literature. This type of research is a systematic literature review. The sample in this study was 17 articles using the prism diagram method. Article retrieval was carried out using the Sage Journal search engine, PubMed, ProQuest, Google Scholar. Based on the results obtained positive and negative impacts of the use of robotic technology in nursing services. Positive impacts include aspects of mobilization, psychology, independent needs, nutritional fulfillment, safety, logistical needs, time management. However, the main challenges include economic, psychological, management, collaboration, social values. These studies meet the five assessments of service quality; Physical appearance, reliability, responsiveness, assurance, empathy. Apart from these five assessments, there are economic, management, collaboration challenges that need to be considered